Primary sclerosing cholangitis - Lemmer, Eric Richard (Department of Medicine, 2017)
Thirty six consecutive patients with primary sclerosing cholangitis (PSC), 20 males median age 42 years, were studied in order to define prognostic variables and determine the influence of surgery on outcome. Presentation was usually with insidious cholestasis or recurrent cholangitis. Twenty six patients (72 per cent) had associated inflammatory bowel disease (ulcerative colitis 20, Crohn's disease 2, unclassified 4). Thirty two patients were followed prospectively for up to nine years. Twenty three remained either stable or had slowly progressive disease. Of the remaining nine patients, seven died (five from end-stage liver failure and two from cholangiocarcinoma) and two patients underwent liver transplantation. Actuarial survival at five years was 52 per cent. A raised serum bilirubin concentration was the only variable at presentation that independently predicted a poor outcome. Cholangiograms were available for detailed assessment in thirty PSC patients. Neither the extent of biliary involvement nor the presence of surgical correctable ("dominant") strictures in the extrahepatic ductal system were of prognostic importance. Six patients who developed obstructive jaundice associated with advanced liver disease underwent surgical drainage operations for dominant biliary strictures, but this did not seem to prevent progression of the disease. Two patients who progressed to end-stage liver disease went on to liver transplantation and were alive with functioning grafts at seven and fourteen months respectively. Nine patients with asymptomatic PSC were followed prospectively for up to twelve years. None of these patients developed overt liver disease but serum bilirubin levels became mildly elevated in two patients. It is concluded that symptomatic PSC is a progressive disease with a poor prognosis. Patients with advanced liver disease due to PSC should be considered directly for liver transplantation. In contrast, asymptomatic PSC patients may remain symptom-free for many years.